2018
DOI: 10.1016/j.neubiorev.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The cingulum bundle: Anatomy, function, and dysfunction

Abstract: HighlightsDetailed descriptions of connections comprising the cingulum bundle.Impact of cingulum bundle damage in rats, monkeys, and humans.Imaging evidence of cingulum abnormalities in multiple psychiatric conditions.Analyses of changing functions along the length of the cingulum.Contrasting effects of fornix and cingulum bundle damage on cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
421
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(477 citation statements)
references
References 345 publications
(587 reference statements)
20
421
2
6
Order By: Relevance
“…In addition, we observed positive associations between LMI and white matter regional volumes. These associations with white matter volume were found in regions overlapping with the following tracts: anterior thalamic radiation (eg, superior frontal gyrus), which carries fibres between prefrontal cortex and thalamus and has been related to executive function and planning complex behaviours; cingulum bundle (ie, superior fronto‐medial gyrus and medial cingulate gyrus), which interconnects frontal, parietal, and medial temporal sites and relates to emotion, reward, pain, motor, conflict, error detection and memory; inferior fronto‐occipital fasciculus (ie, middle fronto‐orbital gyrus and putamen), a long association bundle that connects occipital cortex, temporobasal areas and superior parietal lobe to the frontal lobe and seems to play a key role in visual processing, attention and reading; superior longitudinal fasciculus (eg, inferior parietal gyrus), a large bundle of association fibres connecting the temporal, occipital and parietal lobes with ipsilateral frontal cortices necessary for language, emotions, memory and attention and corticospinal (two regions within the cerebellum VIII), concerned with motor function from the motor cortex to the spinal cord …”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed positive associations between LMI and white matter regional volumes. These associations with white matter volume were found in regions overlapping with the following tracts: anterior thalamic radiation (eg, superior frontal gyrus), which carries fibres between prefrontal cortex and thalamus and has been related to executive function and planning complex behaviours; cingulum bundle (ie, superior fronto‐medial gyrus and medial cingulate gyrus), which interconnects frontal, parietal, and medial temporal sites and relates to emotion, reward, pain, motor, conflict, error detection and memory; inferior fronto‐occipital fasciculus (ie, middle fronto‐orbital gyrus and putamen), a long association bundle that connects occipital cortex, temporobasal areas and superior parietal lobe to the frontal lobe and seems to play a key role in visual processing, attention and reading; superior longitudinal fasciculus (eg, inferior parietal gyrus), a large bundle of association fibres connecting the temporal, occipital and parietal lobes with ipsilateral frontal cortices necessary for language, emotions, memory and attention and corticospinal (two regions within the cerebellum VIII), concerned with motor function from the motor cortex to the spinal cord …”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that the rCAB may play an important role in ADHD. As a whole, the cingulum bundle spans the frontal, parietal, and medial temporal areas of the brain, as well as links subcortical nuclei to the cingulate gyrus (Bubb et al, 2018). FA in this prominent white matter tract has been implicated as a factor in ADHD symptom severity, as well as a marker of individual differences in neurocognitive development (Bathelt et al, 2019;Cooper et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to differences in DWI analyses, wherein the cingulum is not always delineated in the same way by other tract reconstruction methods. Only some connections encompass the entire length of the tract and different subdivisions of the cingulum display distinct FA measures at different mediallateral positions within the bundle, even in areas of overlap-indicating qualitative changes along the length of the tract (Bubb et al, 2018;Heilbronner and Haber, 2014;. The CAB also consists of projections from the amygdala and thalamic nuclei, and runs close to the inferior longitudinal and uncinate fasciculi.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive imaging studies also investigated the role of cingulate regions in executive control, emotion, pain, and episodic memory, and have reported associative abnormalities in memory decline in the MCI and AD pathogenesis (Bubb, Metzler-Baddeley, & Aggleton, 2018). fMRI studies on the cognitive role of CC have shown increased activity in ACC during tasks involving cognitive controls, such as attention, executive functioning and working memory (Lenartowicz & McIntosh, 2005), while the damage of PCC was found to cause trouble with solving cognitive control tasks (Ries et al, 2006).…”
Section: Significance Of Cingulate Region In Cognitive Functioningmentioning
confidence: 99%